TINJAUAN YURIDIS PERLINDUNGAN HUKUM KORBAN INVESTASI “FIKTIF” MELALUI MEDIA ONLINE BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Josua Halomoan Napitupulu (to-ra, 2021)
The practice of fictitious investment that has recently revived in various modes by utilizing online media, reflects that the Indonesian people do not fully understand the various investments that are legal according to the regulations of the Financial Services Authority (OJK), and Indonesian people still have a culture of laziness to work so they immediately trust and believe in the offer outstanding investment in online media. Law No. 25 of 2007 concerning investment, which broadly distinguishes direct investment from abroad (foreign direct investment / FDI) and investment indirectly. Investment activities are business activities carried out to place funds in the hope that at one time it will get a profit or profit. In essence, investment throughmedia online or it can be said as fictitious investment is also regulated in Article 9 and Article 10 of Law Number 11 Year 2008 concerning Electronic Information and Transactions. Business actors offering products through an electronic system are obliged to provide complete and correct information and business actors conducting electronic transactions may include certification by a Reliability Certification Agency. Keywords: Investment, Fictitious, Electronic Transactions